Anaplastic lymphoma kinase expression and gene alterations in glioblastoma: correlations with clinical outcome. Issue 7 (19th December 2016) - Karagkounis, George; Stranjalis, George; Argyrakos, Theodore; Pantelaion, Varvara; Mastoris, Konstantinos; Rontogianni, Dimitra; Komaitis, Spyridon; Kalamatianos, Theodosis; Sakas, Damianos; Tiniakos, Dina
Abstract : Aims: To study anaplastic lymphoma kinase (ALK) protein expression and possible underlying gene alterations in glioblastoma (GBM), correlating them with clinical outcome. Methods: We studied ALK immunohistochemical expression and fluorescent in situ hybridisation (FISH)-detected ALK gene alterations in 51 GBMs (46 isocitrate dehydrogenase-1 (IDH1) R132H -negative and 5 IDH-mutant (IDH1 R132H -positive)). We compared two anti-ALK antibodies and immunohistochemical detection systems (5Α4/Nichirei Biosciences, D5F3/Ventana). The results were correlated with tumour cell proliferation and clinical outcome. Results: Intense granular cytoplasmic ALK immunostaining was observed in 10/51 (19.61%) GBM and correlated with high Ki67 proliferation index; only 1 in 10 ALK-positive cases displayed multiple alk gene signals by FISH. Moderate ALK immunostaining was observed in 21 (41.17%), weak immunostaining in 5 (9.80%) while 15 (29.42%) cases were negative. p53 was expressed in 26/51 GBM (50.9%) (10% cut-off). IDH1 R132H -negative GBM showed higher ALK expression compared with IDH-mutant GBM (65.2% vs 20%). ALK overexpression was more common in older patients but did not correlate with other clinicopathological variables or patient overall survival. Conclusions: ALK overexpression can be identified in up to 70% of GBMs and does not correlate with underlying alk gene amplification. Despite being more common in rapidly growing, clinically aggressive GBM, ALK overexpression did not show correlation with prognosis in this study.